Genetic evidence from Mendelian randomization links CD40 levels to increased risk of estrogen receptor-positive breast cancer - Junyu Yi; Qingfeng Chen; Xiaoyi Liu; Yan Mao; Yongmei Wang; Meng Lv; Haibo Wang; Yuanyuan Wang (Scientific Reports)
Abstract This study uses Mendelian randomization (MR) to investigate the causal roles of CD40 and CD40L in BC.Data from genome-wide association studies (GWAS) on BC (overall, ER-positive, and ER-negative subtypes) and CD40/CD40L levels were obtained from the IEU database. Causal associations were assessed using the inverse-variance weighted (IVW) method, with additional robustness checks performed via MR-Egger, weighted median, and weighted mode methods. Sensitivity analyses, including Cochran’s Q test and MR-PRESSO, were conducted to assess heterogeneity and pleiotropy. Reverse MR analyses were also performed to examine if BC influences CD40/CD40L levels.A borderline significant association was found between CD40 levels and overall BC risk (IVW OR 1.027, 95% CI 1.000–1.054, p = 0.049), with a more robust association observed for ER-positive BC (OR 1.048, 95% CI 1.016–1.082, p = 0.003). No significant associations were found between CD40 levels and ER-negative BC. CD40L did not show any significant associations with BC. Reverse MR analysis indicated no causal effect of BC on CD40/CD40L levels. CD40 is causally associated with a borderline increase in overall BC risk and a more significant increase in ER-positive BC risk. These findings suggest a potential role for CD40 in BC, particularly in ER-positive cases.